Rancang Bangun Aplikasi Monitoring Dan Evaluasi Pekerjaan Proyek Pada Bidang Penataan Ruang Di Dinas PU. Cipta Karya Sumenep - Akhmad Akbar Agung; Henry Bambang; Yoppy Maulana (Jurnal Sistem Informasi Universitas Dinamika, 2016)
Dinas PU. Cipta Karya dan Tata Ruang Kabupaten Sumenep as executive agencies wheel development. Bidang penataan ruang became a top priority along with the occurrence of resistance in the city of sumenep, among others, the construction of a drainage channel, local roads and sidewalks. Problems encountered can not do monitoring with respect to time, cost, and project work progress in the field. So in the initial evaluation and identification work difficult, it often causes a delay in the implementation of the project work. To overcome the obstacles faced by bidang penataan ruang, can be done by means of building the application of monitoring and evaluation of the project in bidang penataan ruang di dinas PU. Cipta Karya Sumenep. Monitoring included the time, cost, and work progress. If there is a mismatch of the project, the system will give an alert/notification to immediately followed up. The results of monitoring will be evaluated by the system for each stretch out. So if there is a discovery that could harm the project can be identified since the beginning. At this stage of implementation, the application indicates conformity with the expectation of 100% and worth to be used. Based on test data planning and realization, obtained results information monitoring and evaluation of each project is presented in the form of the curve S.